Nursing teaching: reflections on the use of conceptual maps in academic practice (Research, Society and Development, 2020)
This study aims to share reflections on the making of concept maps in an academic practice in the undergraduate nursing course at the University of Vale do Taquari. This is a descriptive and exploratory research with a qualitative approach conducted with twenty-five participants. Participants were students regularly enrolled in the Adult and Elderly I Nursing discipline of the undergraduate nursing course at the University of Vale do Taquari in the second semester of 2019. Data collection occurred through the development of conceptual maps, its discussion under approximations with Moreira (2012) and analysis with approximations of Bardin Content Analysis (2016). The results showed that the concept maps synthesized the main concepts worked in the classroom. Thus, the articulation of concepts, disposition of generating terms, as well as the connections generated by the participants' work, identify the precepts of meaningful learning. Thus, when seeking to understand the realization of the concept maps, it was noticed that the participants built and articulated important concepts about the proposed content, showing evidence of their learning.